New Radiological Approaches in Dental Education - İrem Öztürk; Kaan Orhan (European Annals of Dental Sciences)
Introduction: Developing new approaches by harnessing technological advancements alongside traditional dental education is crucial. The Department of Oral and Maxillofacial Radiology is particularly receptive to novel approaches and advancements both in education and in current practice. Staying close to new approaches and methods in educational materials and techniques is an inevitable necessity for keeping pace with the times.Objective and Method: The aim of this review is to discuss current studies regarding how new radiological approaches in dentistry, particularly artificial intelligence and its products, can provide differences and advantages in the field of education. Additionally, it aims to provide insights into future research and developments. It specifically aims to provide a brief summary of recent studies in this area.Results and Conclusions: In today's technology-driven era, gaining a contemporary perspective on educational materials and methods is highly important. With the changing world, it is necessary and inevitable to be open to new developments in education and to leverage the advancements in technology and software alongside traditional materials in radiology education. In light of the research conducted, there is a need for a greater variety and quantity of studies in the near future to further advance and make progress in this area.